2016
DOI: 10.1111/socf.12323
|View full text |Cite
|
Sign up to set email alerts
|

Temporalities of Victimhood: Time in the Study of Postconflict Societies

Abstract: Natascha Mueller-Hirth 2Researchers in peace and conflict studies have rarely explicitly engaged with time and temporality. This article develops a temporal analysis of victimhood in a mature posttransition society, drawing on qualitative research with victims/survivors of gross human rights violations in South Africa. Two decades after the democratic transition, there is a prevalent understanding that it is finally time for victims to "move on." In contrast to the supposed linear temporality of peace processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…While some studies have shown that acknowledging as a victim of rape can, in some respects, be a positive step in the recovery process, others have identified negative effects of acknowledgment on mental health (see Littleton, Rhatigan, and Axsom ; Mueller‐Hirth ; Wilson and Miller ). We argue that these conflicting findings can be explained, in part, by the fact that mental health outcomes not only arise from labeling an assault “rape” but also from identification as a “victim” and/or “survivor” and from the interaction of these identities with other identities, such as race and gender.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have shown that acknowledging as a victim of rape can, in some respects, be a positive step in the recovery process, others have identified negative effects of acknowledgment on mental health (see Littleton, Rhatigan, and Axsom ; Mueller‐Hirth ; Wilson and Miller ). We argue that these conflicting findings can be explained, in part, by the fact that mental health outcomes not only arise from labeling an assault “rape” but also from identification as a “victim” and/or “survivor” and from the interaction of these identities with other identities, such as race and gender.…”
Section: Introductionmentioning
confidence: 99%
“…In law and jurisprudence, scholars attempt to espouse on the social construction of 'victim' and 'victimhood' designations, how the various legal systems deal with cases and claims of victimization (see Pauley 1986;Harris 1991;Erez et al 2011). In the fields of sociology, politics and conflict studies, scholars focus on enhancing our understanding of the politics of victimhood and victim designations, claims and manifestations, how victimhood is defined, negotiated and contested, both socially and politically (see Kearns & Finchman 2005;Derluyn et al 2015;Jacoby 2015;Mueller-Hirth 2017). Our observation is that regardless of the academic trajectory from which a scholar attempts his/her interrogation of victimhood realities and conceptualization, the core meaning of victimhood appear similar, hence according to Claire Ferguson and Brent Turvey, victimology represents "the scientific study of victims and victimization, including the relationships between victims and offender, investigators, courts, corrections, media and social movements" (2009: 2).…”
Section: Relevant Conceptual Perspectives On Victimhoodmentioning
confidence: 99%
“…(Ortiz, Rettberg 2018), (Aguilar, Ramirez, Vargas, Calle, Vargas, Barrera,. 2015), (Gonzalez, Venturini, Poganietz, Finkenrath, Leal, 2017), (Maconachie 2016), (Zimmermann, 2017), (Granovsky 2017), (McAuliffe, 2017)., (DeTommaso,Lem 2017)y (Mueller, 2017) Colombia, Inglaterra…”
Section: Democraciamentioning
confidence: 99%